Hospital Length of Stay, Charges, and Costs Associated With a Diagnosis of Obesity in US Children and Youth, 2006–2016. Issue 8 (August 2020) - Kompaniyets, Lyudmyla; Lundeen, Elizabeth A.; Belay, Brook; Goodman, Alyson B.; Tangka, Florence; Blanck, Heidi M.
Abstract : Background: Childhood obesity is linked with adverse health outcomes and associated costs. Current information on the relationship between childhood obesity and inpatient costs is limited. Objective: The objective of this study was to describe trends and quantify the link between childhood obesity diagnosis and hospitalization length of stay (LOS), costs, and charges. Research Design: We use the National Inpatient Sample data from 2006 to 2016. Subjects: The sample includes hospitalizations among children aged 2–19 years. The treatment group of interest includes child hospitalizations with an obesity diagnosis. Measures: Hospital LOS, charges, and costs associated with a diagnosis of obesity. Results: We find increases in obesity-coded hospitalizations and associated charges and costs during 2006–2016. Obesity as a primary diagnosis is associated with a shorter hospital LOS (by 1.8 d), but higher charges and costs (by $20, 879 and $6049, respectively); obesity as a secondary diagnosis is associated with a longer LOS (by 0.8 d), and higher charges and costs of hospitalizations (by $3453 and $1359, respectively). The most common primary conditions occurring with a secondary diagnosis of obesity are pregnancy conditions, mood disorders, asthma, and diabetes; the effect of a secondary diagnosis of obesity on LOS, charges, and costs holds across these conditions. Conclusions: Childhood obesity diagnosis-related hospitalizations, charges, and costs increased substantially during 2006–2016, and obesity diagnosis is associated with higher hospitalization charges and costs. Our findings provide clinicians and policymakers with additional evidence of the economic burden of childhood obesity and further justify efforts to prevent and manage the disease. Abstract : Supplemental Digital Content is available in the text.